2016
DOI: 10.1002/2016jd024844
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene suppression of new particle formation: Potential mechanisms and implications

Abstract: Secondary aerosols formed from anthropogenic pollutants and natural emissions have substantial impacts on human health, air quality, and the Earth's climate. New particle formation (NPF) contributes up to 70% of the global production of cloud condensation nuclei (CCN), but the effects of biogenic volatile organic compounds (BVOCs) and their oxidation products on NPF processes in forests are poorly understood. Observations show that isoprene, the most abundant BVOC, suppresses NPF in forests. But the previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 112 publications
(177 reference statements)
5
67
0
Order By: Relevance
“…Currently, it is not clear what chemical mechanisms are behind the suppression of NPF in isoprene‐dominated forests. S. H. Lee et al () showed that in the case of the Alabama forest, there were sufficient precursors such as sulfuric acid, ammonia, amines, and relatively low CS , all comparable to the conditions that should allow NPF to take place. Furthermore, they found that there was a clear formation of sub‐3‐nm particles, which were strongly correlated to sulfuric acid concentrations, but these clusters did not grow further.…”
Section: Npf Observations In Various Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it is not clear what chemical mechanisms are behind the suppression of NPF in isoprene‐dominated forests. S. H. Lee et al () showed that in the case of the Alabama forest, there were sufficient precursors such as sulfuric acid, ammonia, amines, and relatively low CS , all comparable to the conditions that should allow NPF to take place. Furthermore, they found that there was a clear formation of sub‐3‐nm particles, which were strongly correlated to sulfuric acid concentrations, but these clusters did not grow further.…”
Section: Npf Observations In Various Environmentsmentioning
confidence: 99%
“…One feature of the nighttime NPF is that it often takes place after the sunset when air masses are influenced by the transported SO 2 plumes. For example, intense bursts of nuclei mode particles were observed in rural forests in Michigan and Alabama with elevated SO 2 concentrations (at ppbv), while NPF did not occur even during the daytime under low or moderate SO 2 concentrations (at sub‐ppbv; Kanawade et al, ; Lee et al, ). It was hypothesized that some heterogeneous oxidation processes can produce sulfuric acid on small particles (Lee et al, ), similarly to those found on cloud and fog droplets (Finlayson‐Pitts & Pitts, ; Seinfeld & Pandis, ) and acidic aerosol particles (Hung & Hoffmann, ; Stangl et al, ).…”
Section: Npf Observations In Various Environmentsmentioning
confidence: 99%
“…The multi-year observations reported here confirm that NPF is uncommon, at least at this forest site in central Amazonia. Some hypotheses to explain the scarcity of NPF and subsequent growth events in the Amazon are as follows: (i) the concentration of inorganic precursors like SO 2 and NH 3 are relatively low, typically < 0.1 ppb (Andreae et al, 1990;Rizzo, unpublished dataset) and < 0.8 ppb (Trebs et al, 2004) in the wet season, respectively; (ii) NPF is inhibited by high emissions of isoprene (Kanawade et al, 2011;Kiendler-Scharr et al, 2009;Lee et al, 2016); (iii) NPF is inhibited by high relative humidity levels (Bonn and Moortgat, 2003;Hamed et al, 2011;Hyvönen et al, 2005); (iv) there are point sources of new particle formation, instead of regional sources, so that subsequent growth to the accumulation mode cannot be followed (Vana et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, TOMAS-VBS does not track the MT and isoprene oxidation products once they enter the VBS scheme separately from the products of other precursors, and further oxidation of these products follows the k OH assumptions above. Although this assumption may be reasonable for MTs, studies in isoprene-dominated forests have shown that NPF appears to be suppressed in the regions studied even when monoterpene emissions are sufficiently high (Bae et al, 2010;Kanawade et al, 2011;Pillai et al, 2013;Haller et al, 2015;Yu et al, 2015;Lee et al, 2016). Hence, the products of 10 isoprene oxidation likely do not age similar to monoterpenes (e.g., Krechmer et al, 2015), but we do not account for this possible effect in our model.…”
Section: Model Descriptionmentioning
confidence: 83%